Pahlawan Qarin: The Concept of Collaborative Learning Game Environment in the Understanding and Translation of the Quran among Youngsters - Mohamed, Juliana; Roslan, Rosfuzah (Journal of Quranic Sciences and Research, 2021)
Computer game can be ’engaging’ learning resources, motivators and interest drivers and, as a consequence, an efficient way to enhance student learning and success in everyday educational practice. These computer game inspire youngsters specially to work incredibly hard, earning even-needed practice repeatedly. Research has consistently shown that game-based learning (GBL) is a way of engaging users and appealing to various modes of learning. Pahlawan Qarin is a game-based framework designed to serve as a way of understanding and interpreting Al Quran to understand its meaning and use in everyday life. It is presented as a ’desktop’ (Personal Computer) game featuring a collaborative learning game (CLG) in which more than one player can play in a group or room using the internet link (network) simultaneously (multiplayer feature). It can be used as an aid tool for teachers in the recitation and education of the Al Quran subject, which is also taught in schools in Islamic Studies. When collaboration with other partners is carried out, youngsters are seen to be highly active in a game playing session, thus motivating them to complete any assignment given.